Quality and correlates of medical record documentation in the ambulatory care setting - Simon Steven R; Kleinman Kenneth P; Soto Carlos M (BMC, 2002)
Abstract Background Documentation in the medical record facilitates the diagnosis and treatment of patients. Few studies have assessed the quality of outpatient medical record documentation, and to the authors' knowledge, none has conclusively determined the correlates of chart documentation. We therefore undertook the present study to measure the rates of documentation of quality of care measures in an outpatient primary care practice setting that utilizes an electronic medical record. Methods We reviewed electronic medical records from 834 patients receiving care from 167 physicians (117 internists and 50 pediatricians) at 14 sites of a multi-specialty medical group in Massachusetts. We abstracted information for five measures of medical record documentation quality: smoking history, medications, drug allergies, compliance with screening guidelines, and immunizations. From other sources we determined physicians' specialty, gender, year of medical school graduation, and self-reported time spent teaching and in patient care. Results Among internists, unadjusted rates of documentation were 96.2% for immunizations, 91.6% for medications, 88% for compliance with screening guidelines, 61.6% for drug allergies, 37.8% for smoking history. Among pediatricians, rates were 100% for immunizations, 84.8% for medications, 90.8% for compliance with screening guidelines, 50.4% for drug allergies, and 20.4% for smoking history. While certain physician and patient characteristics correlated with some measures of documentation quality, documentation varied depending on the measure. For example, female internists were more likely than male internists to document smoking history (odds ratio [OR], 1.90; 95% confidence interval [CI], 1.27 - 2.83) but were less likely to document drug allergies (OR, 0.51; 95% CI, 0.35 - 0.75). Conclusions Medical record documentation varied depending on the measure, with room for improvement in most domains. A variety of characteristics correlated with medical record documentation, but no pattern emerged. Further study could lead to targeted interventions to improve documentation.